2008
DOI: 10.1002/ca.20710
|View full text |Cite
|
Sign up to set email alerts
|

The anatomical variations of the extensor tendons to the dorsum of the hand

Abstract: To lead a quality life, tendon repair must be performed in a trauma causing damage to the extensor tendon of the hand. The aim of this study is to study the structures that can be used as donor tendons. Fifty-four dissected adult hands were examined to study the pattern of the extensor tendons on the dorsum of the hand. The most common distribution patterns of the extensor tendons of the fingers were as follows: a single extensor indicis proprius (EIP) tendon which inserted ulnar to the extensor digitorum (ED)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
32
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 27 publications
4
32
1
1
Order By: Relevance
“…Celik S et al [12] reported single tendon to middle finger in 92.6%.Contrary to this in our study, ED to middle finger existed singly in 58.6%, double tendon in 25.7% and triple tendons in 15.7% specimen.…”
Section: Discussioncontrasting
confidence: 93%
See 3 more Smart Citations
“…Celik S et al [12] reported single tendon to middle finger in 92.6%.Contrary to this in our study, ED to middle finger existed singly in 58.6%, double tendon in 25.7% and triple tendons in 15.7% specimen.…”
Section: Discussioncontrasting
confidence: 93%
“…The types of JT were reported by many authors [ Table.4]. Celik S et al [12] reported thickest type of JT between ring and little finger in 90% of specimens. Govsa et al [18] stated that the thickest type of intertendinous connection in 4 th IMCS was seen in 90% of specimens and also the 4 th IMCS tendons have greatest tendon length and therefore it is a suitable donor graft tissue for local tendon repair.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Developmental defect in different stages of gestation is one of the reasons of the anatomical variations. Besides, various changes of extensor limb myotomes involved in the transformation of the somatic layer of lateral mesoderm; such as regression, retention, or reappearance may be the cause of variations of the tendons (6).…”
Section: Discussionmentioning
confidence: 99%